Exploring Farmers' Decision in Utilizing Certified Palm Oil Seeds in Riau Province - Susanti, Ervin Nora; Ariyanto, Anto (Jurnal Manajemen & Agribisnis, 2023)
Riau Province is the largest center for smallholder palm oil plantations in Indonesia. The productivity of smallholder palm oil plantations is relatively lower compared to private and state plantations due to the low use of certified seeds. This study aims to describe the characteristics of smallholder oil palm businesses and analyze the decisions of smallholders in Riau Province regarding the use of certified oil palm seeds. This research utilized logistic regression analysis. The data used in this study were from the 2014 plantation business household survey conducted by BPS. The number of respondents was 1146 households. The results showed that the variable number of family members significantly negatively affected farmers' decisions to use certified oil seeds. On the other hand, the variables of age, education, capital, farmer groups, and partnership patterns positively influenced farmers' decisions to use certified oil seeds. Meanwhile, the variables of land area, type of land, assistance, and agricultural extension did not affect farmers' decisions to use certified palm oil seeds. Therefore, the decision of smallholders to use certified oil palm seeds is influenced by the number of dependents, age, education, capital, membership of farmer groups, and partnership patterns. Keywords: certificated seed, farmer decision, logistic regression, palm oil, smallholder